Tertiary Students And Their Level Of Understanding Regarding Computer Crimes - Moy, Loh Ah (2001)
In this research , the writer tries to determine the level of understanding of computer crimes among tertiary students and to test the hypothesis that the level of understanding is dependent on the level of tertiary education attained, the frequency of I